Performance analysis of a wireless communication system with smart antenna - Sarker, Andre; Hamim-Al-Ahsan (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.